Lensing in the Ultrasonic Domain using Negative Refraction Induced by Material Contrast - C. T. Manjunath (Nature Portfolio, 2019)
Abstract The focusing of ultrasound using topographic lenses, typically made of plates with step changes that cause an interaction between forward- and backward-propagating guided waves, has been widely studied in recent years. However, such ‘step-change’ lenses require precise machining and moreover, the thick-thin structure can be unstable during deployment in practical inspection applications. The work reported here follows from the insight that perhaps any approach to induce a mismatch in acoustical impedance as achieved by the step-change can also lead to focusing of ultrasonic guided waves. By carefully choosing the impedance pairing, a novel material contrast lens stacking Aluminium and Molybdenum plates in series is shown to achieve focusing of ultrasound through negative refraction. The interface between the two metals causes the interaction of the forward-propagating second symmetric Lamb mode S2 into the backward- propagating first symmetric S2b. The focusing of Lamb waves is demonstrated using numerical simulations validated by experiments. Comparison with a simple Aluminium-Aluminium plate combination brings out the underlying physics of focusing using the proposed material contrast lens. Simulation results showing super-resolution imaging using the proposed material contrast lens  are also presented, demonstrating the power of the proposed approach. This report opens up the possibilities of developing new lensing devices for use in medical imaging and nondestructive evaluation, among other possible applications.